Dear SIR: smart interactive research tool for beginners / Siti Daleela Mohd Wahid ... [et al.] - Mohd Wahid, Siti Daleela; Abu Hasan, Norraidah; Hasan, Ahmad Sapuan; Rezali @ Abdul Sukor, Norzianis; Mohammed Khalid, Sulaiman; Amiruddin, Nadia Hanum (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Covid-19 pandemic has changed the way how a classroom lecture being conducted. Direct physical interactions are no longer a norm. This includes how the information is accessed. Researchers who are not ready to adapt new norm may takes longer time to finish his research, lost direction on where his research supposed to end, or simply give up. Therefore, we initiate and create Dear SIR that makes learning interactive, simpler, and combined theoretical and practical, and more effective. Dear SIR is a mobile application which acted as a research alternative tool to ensure teaching & learning (T&L) more interesting and interactive. We developed Dear SIR application with an objective to assist university’s students and amateur researchers to understand the basic idea of research processes. Even though, there are numerous of research aid available in the market, but none of them practically guide the student to comprehend how to identify and align the research issues, objectives, questions, hypotheses, and framework development. The idea for product development derived from an in-depth discussion based on our own experience during our doctoral study period. No one guide us on how to identify all research elements when we read an article or develop our research. Surprisingly, very limited comprehensive research application can be obtained to lead us on how to classify the most crucial elements of research. Therefore, we realising this idea and starting to develop Dear SIR research tool. Evidently, the Dear SIR utilized the concept of “finding pieces of the puzzle and putting it together” to understand the complex research process to assist students and amateur researchers.